(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In this article, the authors argue that by the new century, the character of all types of propaganda has fundamentally changed, that propaganda has become a powerful tool used on a global scale for the purpose of various social groups and political forces, and that these changes in the propaganda system are taking place under the influence of a number of social processes, trends, and factors.